Phc Transformation Through Physiological Literacy-Based Community Education: Integrating Biomedical Understanding, Health Promotion, and Preventive Care for Sustainable Community Health - M. Hamdani; Subhan Muhith; M Iman Tarmizi Thaher; Rahma Zakiah Al Hamdnai; Melawati (International Journal of Contemporary Sciences (IJCS), 2026)
Primary Health Care (PHC) remains the foundation of global health systems, emphasizing prevention, community participation, and equitable access to healthcare services. However, many PHC interventions continue to face challenges in achieving sustainable behaviour change because health education frequently focuses on recommendations without improving community understanding of underlying physiological mechanisms. This study aims to develop a physiological literacy-based community education model to strengthen PHC transformation by integrating biomedical understanding, health promotion principles, and preventive healthcare strategies. A conceptual synthesis approach was conducted by integrating evidence from primary healthcare, physiological literacy, health promotion theory, behavioural science, and community-based education. Key concepts were analysed to identify how understanding human body functions can improve health awareness, motivation, and long-term behavioural change